UPTAKE OF NICKEL(II) USING DIMETHYLGLIOXYME CHELATE ANION EXCHANGE RESIN - Nugraheni, Nugraheni VD; Gunawan, Gunawan; Junaedi, Cholik Muhammad (JURNAL SAINS DAN MATEMATIKA, 2010)
ABSTRACT—Uptake of nickel(II) ions from solution are studied using strong base anion resin ( Lewatit M500, counter ions of Cl-) and dimethylglyoxime (2,3-butanedione dioxime, H2DMG) as chelating agent. This study was conducted to determine optimum condition of chelate resin preparation for uptake of nickel(II) ions from solution. The research used batch and column techniques. Batch technique was used to determine the best contact time at chelate resin preparation, capacity of chelate resin ( mg Ni2+/ g), effect of pH stripping (pH 1- 5) and pH of nickel(II) solution (pH 4 - 10) to capacity of chelate resin as well as effect of pH backwash (pH 1- 5) to percentage of nickel(II) ions recovery. Column technique was used for uptake of nickel(II) ions from waste water of industrial of metal veneering. Column flow rate was kept constant at 2 mL/ minute. Nickel(II) ions which were not removed by chelate resin was quantitatively analyzed with atomic absorption spectrophotometer at wavelength of 232,00 nm. Result of the research revealed the best contact time at chelate resin preparation was 120 - 240 minutes for variation of contact time from 0 to 240 minutes to each 25 gram strong base anion resin. Capacity of chelate resin was obtained about 0,209 to 0,214 mg Ni2+/ g chelate resin. Capacity of chelate resin decreased progressively after process of stripping that was 0,217 - 0 mg Ni2+/ g from pH of 5 to 1. The best range pH of nickel(II) solution was obtained at pH of 6 to 7 with capacity of chelate resin from 0,239 to 0,241 mg Ni2+/ g and selected at pH 6. Percentage recovery of nickel(II) ions increased 21,966 to 75,314% from pH backwash of 5 to 1. With column technique, chelate resin capacity was obtained 0,208 mg Ni2+/ g and breakthrough point was reached when flow times reached in 60 to 80 minutes.Permalink : http://ejournal.undip.ac.id/index.php/sm/article/view/2854